Lignocellulosic composition based thermal kinetic study of Mangiferaindica Lam, Artocarpus Heterophyllus Lam and Syzygium Jambolana seeds - Pal D.B.; Srivastava N.; Pal S.L.; Kumar M.; Syed A.; Elgorban A.M.; Singh R.; Gupta V.K. (My University, 2025)
In the present study, pyrolysis of mangifera indica L., Artocarpus heterophyllus L. and jambolana seeds have been performed using thermogravimetric analysis. These biomasses have enriched lignocellulosic composition of hemicellulose (5–10%) and lignin (1–3%) which are unexplored. The TGA analysis was performed at various heating rates of 10, 15, 20, 25 and 30 °C/min from 25 to 600 °C. Kinetic investigation of the pyrolysis method using TGA statistics has been done using iso-conversional models of Flynn-Wall-Ozawa, Kissinger-Akahira-Sunose, Vyazovkin and Vyazovkin AIC. The apparent activation energies value ranged from 179.86 to 226.31 kJ/mol in the fractional conversion range of 0.1 to 0.7. © 2021 Elsevier Ltd